Assessment of Antibiotic Prophylaxis in Surgical Patients and Association Factors at Thu Duc District Hospital, Ho Chi Minh City, Vietnam in 2018 - Phan Van Tuong; Chu Huyen Xiem; Nguyen Chi Anh; La Ngoc Quang (SAGE Publishing, 2021)
Surgical antibiotic prophylaxis (SAP) is considered an important interventional tool for antimicrobial resistance. Guideline compliance was poor across different countries and this results in an inappropriate and overuse of antibiotics. The study was cross-sectional, combining qualitative and quantitative. The Research used the MOH's Antibiotic Preventive Medicine Guidelines as the standard to verify surgical preventive treatment compliance from patient medical records. Research performed on 373 medical records with surgical indications. The study was conducted from January to June 2019. Data were entered using Epidata software and processed by SPSS software version 19.0. Analysis: calculating OR for related factors. The compliance rate of using prophylactic antibiotics was 83.1%. There is a relationship between the type of incision, the length of time surgery, and compliance with surgical prophylactic use of antibiotics ( P  < .05). Barriers to adherence to prophylactic antimicrobial therapy include: overcrowding patients, health-care workers "broad-spectrum antibiotic use habits, and health-care workers" views on surgical and muscle environment, the material was not completely sterilized.